Plasticity of Intact Rubral Projections Mediates Spontaneous Recovery of Function after Corticospinal Tract Injury - Siegel, Chad S. (J Neurosci, 2015)
Axons in the adult CNS fail to regenerate after injury, and therefore recovery from spinal cord injury (SCI) is limited. Although full recovery is rare, a modest degree of spontaneous recovery is observed consistently in a broad range of clinical and nonclinical situations. To define the mechanisms mediating spontaneous recovery of function after incomplete SCI, we created bilaterally complete medullary corticospinal tract lesions in adult mice, eliminating a crucial pathway for voluntary skilled movement. Anatomic and pharmacogenetic tools were used to identify the pathways driving spontaneous functional recovery in wild-type and plasticity-sensitized mice lacking Nogo receptor 1. We found that plasticity-sensitized mice recovered 50% of normal skilled locomotor function within 5 weeks of lesion. This significant, yet incomplete, spontaneous recovery was accompanied by extensive sprouting of intact rubrofugal and rubrospinal projections with the emergence of a de novo circuit between the red nucleus and the nucleus raphe magnus. Transient silencing of this rubro–raphe circuit in vivo via activation of the inhibitory DREADD (designer receptor exclusively activated by designer drugs) receptor hM4di abrogated spontaneous functional recovery. These data highlight the pivotal role of uninjured motor circuit plasticity in supporting functional recovery after trauma, and support a focus of experimental strategies on enhancing intact circuit rearrangement to promote functional recovery after SCI.